Anatomy and spatial organization of Müller glia in mouse retina. Issue 8 (1st June 2017) - Wang, Jingjing; O'Sullivan, Matthew L.; Mukherjee, Dibyendu; Puñal, Vanessa M.; Farsiu, Sina; Kay, Jeremy N.
Abstract: Müller glia, the most abundant glia of vertebrate retina, have an elaborate morphology characterized by a vertical stalk that spans the retina and branches in each retinal layer. Müller glia play diverse, critical roles in retinal homeostasis, which are presumably enabled by their complex anatomy. However, much remains unknown, particularly in mouse, about the anatomical arrangement of Müller cells and their arbors, and how these features arise in development. Here we use membrane‐targeted fluorescent proteins to reveal the fine structure of mouse Müller arbors. We find sublayer‐specific arbor specializations within the inner plexiform layer (IPL) that occur consistently at defined laminar locations. We then characterize Müller glia spatial patterning, revealing how individual cells collaborate to form a pan‐retinal network. Müller cells, unlike neurons, are spread across the retina with homogenous density, and their arbor sizes change little with eccentricity. Using Brainbow methods to label neighboring cells in different colors, we find that Müller glia tile retinal space with minimal overlap. The shape of their arbors is irregular but nonrandom, suggesting that local interactions between neighboring cells determine their territories. Finally, we identify a developmental window at postnatal Days 6 to 9 when Müller arbors first colonize the synaptic layers beginning in stereotyped inner plexiform layer sublaminae. Together, our study defines the anatomical arrangement of mouse Müller glia and their network in the radial and tangential planes of the retina, in development and adulthood. The local precision of Müller glia organization suggests that their morphology is sculpted by specific cell to cell interactions with neurons and each other.